2016
DOI: 10.1002/eej.22866
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Recovery Characteristics after High‐Frequency Current Interruption in Vacuum Circuit Breaker

Abstract: SUMMARY When the contacts of circuit breaker are opened just before current zero, the gap between contacts will still be very short. Therefore, it cannot withstand recovery voltage between the contacts. In such a case, multiple reignition is likely to take place. Many investigators had tried to clarify this phenomenon, and many reports have been published. However, high‐frequency current interruption and dielectric recovery characteristics are related to some parameters (value of current, arc time, and so on).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…After that, i CB drops to zero stepwise. This phenomenon is called "current chopping", being known to cause a switching charge in v CB [17,18]. As can be seen from Fig.…”
Section: Experimental Results Without Rc Snubbermentioning
confidence: 99%
See 1 more Smart Citation
“…After that, i CB drops to zero stepwise. This phenomenon is called "current chopping", being known to cause a switching charge in v CB [17,18]. As can be seen from Fig.…”
Section: Experimental Results Without Rc Snubbermentioning
confidence: 99%
“…On the other hand, switching surge of VCB has to be properly suppressed to prevent re-ignition. It is reported that the switching surge can be suppressed by connecting an RC snubber circuit (CR surge suppressor) in parallel to VCB [18]. Thus, we evaluate operating characteristics with and without RC snubber circuit.…”
Section: Experimental Systemmentioning
confidence: 99%